2014
DOI: 10.1097/ccm.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and 1-Year Outcomes in Older Americans With Severe Sepsis*

Abstract: Objectives While critical care physicians view obesity as an independent poor prognostic marker, growing evidence suggests that obesity is, instead, associated with improved mortality following ICU admission. However, this prior empirical work may be biased by preferential admission of obese patients to ICUs, and little is known about other patient-centered outcomes following critical illness. We sought to determine whether one-year mortality, health care utilization, and functional outcomes following a severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 49 publications
10
111
3
Order By: Relevance
“…The ICU mortality in critically ill patients with a BMI ≥25 kg/m 2 depends primarily on the number of organ failures, especially when two or more organs are affected. The incidence of high BMI in patients enrolled in the present study was higher than those described by other authors, who have report- ed an incidence ranging from 5-25% (5,7,8,14,(25)(26)(27), similar to the data shown in the national health survey of 2012. In the general population, an increase in the incidence of oncologic diseases was observed, which may be associated with the advent of new diagnostic techniques and treatment protocols for oncologic patients, thus allowing an improvement of the survival rate.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The ICU mortality in critically ill patients with a BMI ≥25 kg/m 2 depends primarily on the number of organ failures, especially when two or more organs are affected. The incidence of high BMI in patients enrolled in the present study was higher than those described by other authors, who have report- ed an incidence ranging from 5-25% (5,7,8,14,(25)(26)(27), similar to the data shown in the national health survey of 2012. In the general population, an increase in the incidence of oncologic diseases was observed, which may be associated with the advent of new diagnostic techniques and treatment protocols for oncologic patients, thus allowing an improvement of the survival rate.…”
Section: Discussioncontrasting
confidence: 52%
“…Several authors have described that patients without cancer with certain degrees of obesity have better survival to clinical conditions that endanger life during the ICU stay, which has been defined as paradoxical obesity (15,26,27). In contrast, the results of the present study, which included only critically ill oncologic patients, failed to establish an association between high BMI and better prognosis in ICU; therefore, the ICU mortality of patients with BMI < 25 kg/m 2 and ≥ 25 kg/m 2 was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a recent retrospective study of 792 patients with severe sepsis showed that the survival rate of morbidly obese patients was twofold better than underweight and normal-weight patients. 53 The protective study of Prescott et al 52 examined the association of BMI with mortality rate in 1,404 patients with severe sepsis and showed that obesity was, in fact, associated with improved shortterm (90 days) and long-term (1 year) mortality in older patients. 52 Although unanimous, these investigations performed in ICU setting contradict other findings showing that obesity is a risk factor for increased mortality in pandemic viral infections such as the H1N1 viruses.…”
Section: Obesity Sepsis and Icu Mortalitymentioning
confidence: 98%
“…In a separate analysis by Prescott et al, patients with severe sepsis that were obese (OR ¼ 0.59, 95% CI 0.39e0.88) and severely obese (OR 0.46, 95% CI 0.26e0.88) had a lower risk of death at 1 year than normal weight patients. However, obese patients were noted to have greater Medicare expenditures [24]. Our analysis suggests that patients with excess BMI may be more likely to develop respiratory or renal failure, potentially leading to increased healthcare expenditures.…”
Section: Discussionmentioning
confidence: 71%